Translational Research Techniques for the Facial Plastic Surgeon: An Overview - Mason, William; Levin, Albert M.; Buhl, Katherine; Ouchi, Takahiro; Parker, Bianca; Tan, Jessica; Ashammakhi, Nureddin; Jones, Lamont R. (Facial Plastic Surgery, 2023)
The field of facial plastic and reconstructive surgery (FPRS) is an incredibly diverse, multispecialty field that seeks innovative and novel solutions for the management of physical defects on the head and neck. To aid in the advancement of medical and surgical treatments for these defects, there has been a recent emphasis on the importance of translational research. With recent technological advancements, there are now a myriad of research techniques that are widely accessible for physician and scientist use in translational research. Such techniques include integrated multiomics, advanced cell culture and microfluidic tissue models, established animal models, and emerging computer models generated using bioinformatics. This study discusses these various research techniques and how they have and can be used for research in the context of various important diseases within the field of FPRS.
Keywords: translational research; multiomics; facial plastic and reconstructive surgery; keloid disease